ST TEGI PENGEMBANGAN PERG"URUAN TINGGI KEOLAHRAGAAN MENGHADAPI TANTANGAN MASA DEPAN : tudi Kasus Fakultas limo Keolahragaan UNY - Dimyati, Dimyati (Jurnal Cakrawala Pendidikan, 2016)
The globalization has revieled the fast growing complexity in our society. If, there fore, is of crucial importance for society, including high institution ofsport discipline, to adopt tangible paradigm and strategy so as to remain keeping abreast with all dynalnics. The high institution of sport discipline having no sense of future and dynamic anticipationof merely equipping itself with temporary reaction will be crushed by the changes in our sociaty and, in tum, it will gradually"die out". Welcoming this challeging globalitation era, the high institution of sport discipline is left behind in tenns of its human recaurses aspecton studies of sport, science development. The high institution of sport discipline has not yet shown is capability to statify the society’s need. The development of science and tecnology in the high institution of sport discipline has been experiencing slow development in to comparison to the development of sport world. Four strategies need developing to face the future challenge the high institution of spoet discipline, firstly, carrying out changeover management syitematically, totally,essentially with " the main goal of the renewed orientation. Scondly, developing the academic, quality.T/lirdely, translating the concept of link and match into reality according to what society needs. Finally, developing national and international role in having concern on high institution of sport discipline and national and international sport organizations.